Big data driven supply chain design and applications for blockchain: An action research using case study approach. (July 2021) - Sundarakani, Balan; Ajaykumar, Aneesh; Gunasekaran, Angappa
Highlights: Application of blockchain and big data analytics in the field of supply chain management is nascent at present. The research method used in this study involves a combination of an Action Research method and Case Study research. Case Study A examined the blockchain application in cross-border cargo movements, which reveals the need of digital blockchain backbone and associated system connections. Case Study B investigated the application in a liquid chemical logistics company, which leverages the blockchain technology providing range of benefits and efficiencies. The research supports the Resource Based View (RBV) theory and recommendations are provided in terms of regulating the blockchain-bigdata-supply chain interference through guidelines and framework. Abstract: Blockchain appears to still be nascent in its growth and a relatively untapped asset. This research investigates the need of blockchain in Industry 4.0 environment from Big Data perspective in supply chain management. The research method used in this study involves a combination of an Action Research method and Case Study research. More specifically, the action research method was applied in two industry case studies that implemented and tested the designed architecture in a global logistics environment. Case Study A examined the blockchain application in cross-border cargo movements whereas Case Study B investigated the application in a liquid chemical logistics company serving to petroleum industries. Our research analysis has identified that the Case A subject had disconnected systems and services for blockchain wherein the big data interactions had failed (failure case). Whereas in Case B, the company has achieved nearly 25% increase in revenue through its customer service after the blockchain implementation and thereby reduction in paperwork and carbon emissions (success case). This research contributes to the advancement of the body of knowledge to big data and blockchain by identifying key implementation guideline and issues for blockchain in supply chain management. Further, action-based research coupled with a case study approach has been used to evaluate the application aspects of the architecture's scalability and functionality of bigdata and blockchain in supply chain management.